Characterization of anti-erythrocyte and anti-platelet antibodies in hemolytic anemia and thrombocytopenia induced by Plasmodium spp. and Babesiaspp. infection in mice - Zhou, Mo; Xie, Jun; Kawase, Osamu; Nishikawa, Yoshifumi; Ji, Shengwei; Zhu, Shanyuan; Cao, Shinuo; Xuan, Xuenan (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria and Babesiosis are acute zoonotic disease that caused by infection with the parasite in the phylum Apicomplexa. Severe anemia and thrombocytopenia are the most common hematological complication of malaria and babesiosis. However, the mechanisms involved have not been elucidated, and only a few researches focus on the possible role of anti-erythrocyte and anti-platelet antibodies. In this study, the Plasmodium yoelii, P. chabaudi, Babesia microti and B. rodhaini infected SCID and ICR mice. The parasitemia, survival rate, platelet count, anti-platelet antibodies, and the level of IFN-γ and interleukin (IL) -10 was tested after infection. Furthermore, the P. yoelii, P. chabaudi , B. rodhaini and B. microti infected ICR mice were treated with Artesunate and Diminaze, the development of the anti-erythrocyte and anti-platelet antibodies in chronic stage were examined. At last, the murine red blood cell and platelet membrane proteins probed with auto-antibodies induced by P. yoelii, P. chabaudi, B. rodhaini, and B. microti infection were characterized by proteomic analysis. The high anti-platelet and anti-erythrocyte antibodies were detected in ICR mice after P. yoelii, P. chabaudi, B. rodhaini, and B. microti infection. Actin of murine erythrocyte and platelet is a common auto-antigen in Plasmodium and Babesia spp. infected mice. Our findings indicate that anti-erythrocyte and anti-platelet autoantibodies contribute to thrombocytopenia and anemia associated with Plasmodium spp. and Babesia spp. infection. This study will help to understand the mechanisms of malaria and babesiosis-related thrombocytopenia and hemolytic anemia.